Reversing sex role reversal: compete only when you must - Silva, K. (2013)
The operational sex ratio (OSR) is thought to be a major factor influencing the intensity of mating competition and sexual selection. Even though many studies on species with conventional sex roles have shown that alterations in the OSR can either intensify male–male competition or promote female–female competitive interactions, sometimes resulting in a reversal of sex roles, it is not known how, and how quickly, individuals with reversed sex roles respond to fluctuations in this ratio. We tested for a direct influence of adult sex ratios (as a direct estimation of the OSR) on the reproductive behaviour of the sex role-reversed black striped pipefish, Syngnathus abaster. Although imbalances in the OSR effectively modulated the expression of sex roles, with males and females varying in the degree of choosiness and competitive displays, alterations in the sex ratios did not promote a similar response pattern in both sexes. A surplus of males resulted in a reversion to conventional sex roles observed when both sexes coexist in similar numbers, with males competing intensely and exhibiting a conspicuous ornament towards other males. An excess of females, in contrast, did not result in an overall increase in female competitive interactions. Only small, less attractive, females were more prone to compete as the proportion of males decreased. Large females, however, seemed to rely on their greater mating prospects, thereby avoiding the hypothetical costs of intrasexual competition.